Genomic Analyses of >3,100 Nasopharyngeal Pneumococci Revealed Significant Differences Between Pneumococci Recovered in Four Different Geographical Regions - van Tonder, Andries J.; Bray, James E.; Jolley, Keith A.; Jansen van Rensburg, Melissa; Quirk, Sigríður J.; Haraldsson, Gunnsteinn; Maiden, Martin C. J.; Bentley, Stephen D.; Haraldsson, Ásgeir; Erlendsdóttir, Helga; Kristinsson, Karl G.; Brueggemann, Angela B. (Frontiers in Microbiology, 2019)
Understanding the structure of a bacterial population is essential in order to understand bacterial evolution. Estimating the core genome (those genes common to all, or nearly all, strains of a species) is a key component of such analyses. The size and composition of the core genome varies by dataset, but we hypothesised that the variation between different collections of the same bacterial species would be minimal. To investigate this, we analysed the genome sequences of 3,118 pneumococci recovered from healthy individuals in Reykjavik (Iceland), Southampton (United Kingdom), Boston (USA) and Maela (Thailand). The analyses revealed a ‘supercore’ genome (genes shared by all 3,118 pneumococci) of 558 genes, although an additional 354 core genes were shared by pneumococci from Reykjavik, Southampton and Boston. Overall, the size and composition of the core and pan-genomes among pneumococci recovered in Reykjavik, Southampton and Boston were similar. Maela pneumococci were distinctly different in that they had a smaller core genome and larger pan-genome. The pan-genome of Maela pneumococci contained several >25 Kb sequence regions (flanked by pneumococcal genes) that were homologous to genomic regions found in other bacterial species. Overall, our work revealed that some subsets of the global pneumococcal population are highly heterogeneous, and our hypothesis was rejected. This is an important finding in terms of understanding genetic variation among pneumococci and is also an essential point of consideration before generalising the findings from a single dataset to the wider pneumococcal population.